Seebeck effect based electro thermal converter - Thangarajah, Jeghan; Chua, Shang Hang; Mohd Zul, Aiman Fahmi; Tharmalingam, Kumarathevan; Hamid, Mahamad (Universiti Teknologi MARA, Kedah, 2018)
We aim to create a device, known as, Seebeck Effect Based Electro Thermal Converter (SEBET Converter) to convert thermoelectric energy into electrical energy. Current hot issues such as wastage of electricity in the form of heat energy and great amount of heat loss in factories are demanding our attention. SEBET Converter can be used to reduce heat loss and generate more electricity effectively. SEBET Converter is produced and functions based on the Seebeck effect. The temperature difference between two dissimilar electrical conductors or semiconductors can produce a voltage difference between the two substances. SEBET Converter uses thermoshield to trap the heat energy while inside SEBET Converter, difference of temperature is generated, and thermoelectric plates are used to convert thermoelectric energy into electrical energy. The electricity produced by SEBET Converter is constant and stable. Heat loss can be reduced, and more electrical energy can be produced using SEBET Converter. SEBET Converter can be used to charge phones and supply electricity to some electrical devices, and, in a bigger size, can be used in factories to convert a huge amount of heat loss into electrical energy. Besides, SEBET Converter is also made using recycle materials, which makes the SEBET Converter an eco-friendly one. To be mentioned, e-waste (waste of electrical products) are used to make SEBET Converter. SEBET Converter can convert thermoelectric energy into electrical energy effectively based on the Seebeck Effect. Therefore, we hope that SEBET Converter can help build a greener environment and an eco-friendly society. We also wish that SEBET Converter can be applied in countries that are short of electricity supply to provide them unlimited electricity source.